2015
DOI: 10.1357/002224015815848820
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen substrate–dependent nitrous oxide cycling in salt marsh sediments

Abstract: Nitrous oxide (N2O) is important to Earth's climate because it is a strong absorber of radiation and an important ozone depletion agent. Increasing anthropogenic nitrogen input into the marine environment, especially to coastal waters, has led to increasing N2O emissions. Identifying the nitrogen compounds that serve as substrates for N2O production in coastal waters reveals important pathways and helps us understand their control by environmental factors. In this study, sediments were collected from a long-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 37 publications
1
37
0
Order By: Relevance
“…Although estuaries are generally assumed to be an N 2 O source, undersaturated surface waters are reported for both areas receiving low N inputs (Liu et al, ; Soued et al, ) and those receiving high enough N inputs to drive the O 2 depletion that triggers denitrification (Borges et al, ; Ji et al, ; Punshon & Moore, ). Here the estuary mouths, which tended to be low in inorganic N and supersaturated in DO, were the most consistent N 2 O sinks.…”
Section: Discussionmentioning
confidence: 99%
“…Although estuaries are generally assumed to be an N 2 O source, undersaturated surface waters are reported for both areas receiving low N inputs (Liu et al, ; Soued et al, ) and those receiving high enough N inputs to drive the O 2 depletion that triggers denitrification (Borges et al, ; Ji et al, ; Punshon & Moore, ). Here the estuary mouths, which tended to be low in inorganic N and supersaturated in DO, were the most consistent N 2 O sinks.…”
Section: Discussionmentioning
confidence: 99%
“…The Great Sippewissett Marsh is limited by N as shown by a comprehensive study on its N budget [ Valiela and Teal , ]. In the experimental plots receiving long‐term fertilization, enhanced primary production, nutrient retention, organic N content, N 2 production, and nitrous oxide production have been documented [ Valiela et al ., , ; Hamersley and Howes , ; Brin et al ., ; Kinney and Valiela , ; Uldahl , ; Ji et al ., ]. These previous studies showed that the various effects of long‐term fertilization were usually more pronounced in extra‐high‐fertilization (XF) plots than in high‐fertilization (HF) plots.…”
Section: Discussionmentioning
confidence: 99%
“…NH 4 + and NO 3 − concentrations in pore water samples were determined as described previously [ Ji et al ., ]. In brief, NO 3 − concentrations were measured in duplicate using a hot (90°C) acidified vanadium (III) reduction column coupled to a Teledyne Chemiluminescence NO/NO x Analyzer (Model 200E), with a detection limit of 0.5 μM [ Braman and Hendrix , ; Garside , ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies in the OMZ have also revealed a remarkable richness of metabolic processes along the redox gradient, as well as novel linkages between community members (Plominsky et al, 2018). Furthermore, stable isotope studies have provided enormous insight into understanding spatio-temporal patterns of production and consumption of different nitrogen species in the OMZ (Sun et al, 2017;Ji et al, 2015a). In these areas, the production of N 2 O varies regionally (Ji et al, 2015b) and seasonally (Farías et al, 2015;Torres-Beltrán et al, 2017;Capelle et al, 2018).…”
Section: Field-based Analysis Of Microbial Communities Involved In N mentioning
confidence: 99%